AN EXTREME VALUE APPROACH IN EXCHANGE RATES MODELLING - MOJSEJ, Ivan; TARTAĽOVÁ, Alena (Journal of Advanced Studies in Finance, 2013)
This paper proposed an extreme value approach to estimate the exchange rates volatility. We analyzed exchange rates of USD/EUR. We applied three models, one is the Block Maxima Method based on Fisher-Tippet theorem and the other is the Peaks over Threshold (POT) Model which models the observed values exceeding a large threshold. The third model is the classical model based on assumption about normal distribution of exchange rates returns. In the first method is important to choose the number of blocks which we made by using graphical methods. In the second method is important to find suitable threshold. The tool is the plot of the sample mean excess function and QQ-plot. The most appropriate model was found by goodness of fit tests, choosing the highest value of the test. Using these three methods we calculated high quantiles of exchange rates and compared results.